High-quality single amplicon sequencing method for illumina MiSeq platform using pool of ‘N’ (0–10) spacer-linked target specific primers without PhiX spike-in - Naik, Tejali; Sharda, Mohak; C P, Lakshminarayanan; Virbhadra, Kumar; Pandit, Awadhesh (BMC genomics, 2023)
Illumina sequencing platform requires base diversity in the initial 11 cycles for efficient cluster identification and colour matrix estimation. This limitation yields low-quality data for amplicon libraries having homogeneous base composition. Spike-in of PhiX library ensures base diversity but reduces the overall number of sequencing reads for data analysis. To overcome such low diversity issues during amplicon sequencing on illumina platforms, we developed a high throughput single amplicon sequencing method by introducing 'N' (0-10) spacers in target gene amplification primers that are pooled for simple handling. We evaluated the efficiency of 'N' (0-10) spacer-linked primers by targeting bacterial 16S V3-V4 region, demonstrating heterogeneous base library construction. The addition of 'N' (0-10) spacers causes sequencing frameshift at every base that leads to base diversity and produces heterogeneous high quality reads within a single amplicon library. We have written a python based command-line software,"MetReTrim", to trim the 'N' (0-10) spacers from the raw reads ( https://github.com/Mohak91/MetReTrim ). We further demonstrated the accuracy of this method by comparative mock community analysis with standard illumina V3-V4 primer method. The ZymoBIOMICS™ microbial community DNA standard was used as a control for this study. We performed data analysisusing the DADA2 pipeline where taxonomy was assigned using SILVA database as reference. We observed no difference between the communities represented by our method and standard illumina V3-V4 primer method. This method eliminates the need for PhiX spike-in for single amplicon sequencing on illumina MiSeq platform. This allows for sequencing of more number of samples in a run and a reduction in the overall cost. Given that Illumina sequencing works on SBS chemistry irrespective of the platform (such as HiSeq, MiSeq, NextSeq, NovaSeq, etc.) we propose that this strategy of using 'N' (0-10) spacer-linked primer design can be adopted for generating high-quality single locus amplicon sequencing in a high throughput manner across the illumina platform subject to further validation.